2016
DOI: 10.1111/rda.12866
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Angus cross beef heifers after GnRH treatment on day 23 and timing of insemination in 14‐day CIDR protocol

Abstract: This study compared artificial insemination pregnancy rate (AI-PR) between 14-day CIDR-GnRH-PGF2α-GnRH and CIDR-PGF2α-GnRH synchronization protocol with two fixed AI times (56 or 72 hr after PGF2α). On day 0, heifers (n = 1311) from nine locations assigned body condition score (BCS: 1, emaciated; 9, obese), reproductive tract score (RTS: 1, immature, acyclic; 5, mature, cyclic) and temperament score (0, calm; and 1, excited) and fitted with a controlled internal drug release (CIDR, 1.38 g of progesterone) inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Thus, acyclic animals have a smaller ovarian size. Results presented in Table 3 are inconsistent with those found by Kasimanickam et al (2016), who observed that the physiological state of the ovarian structures (presence of CL) of the animal at the beginning of the TAI protocol affects the pregnancy rate, that is, cyclic pubertal heifers (CL presence) had better results than the pre-pubertal (acyclic).…”
Section: /7contrasting
confidence: 75%
“…Thus, acyclic animals have a smaller ovarian size. Results presented in Table 3 are inconsistent with those found by Kasimanickam et al (2016), who observed that the physiological state of the ovarian structures (presence of CL) of the animal at the beginning of the TAI protocol affects the pregnancy rate, that is, cyclic pubertal heifers (CL presence) had better results than the pre-pubertal (acyclic).…”
Section: /7contrasting
confidence: 75%
“…Moreover, a high percentage of Bos indicus and cross beef heifers in fixed-time artificial insemination (FTAI) programs have been reported to have immature reproductive tracts (Claro et al, 2010;Kasimanickam et al, 2017). This was associated with a poor pregnancy rate because of the asynchrony between estrus and ovulation (Bó and Baruselli, 2014).…”
Section: Introductionmentioning
confidence: 99%